PENGARUH KOMPETENSI APARATUR DESA, PEMANFAATAN TEKNOLOGI INFORMASI, DAN KEJELASAN SASARAN ANGGARAN TERHADAP PENGELOLAAN DANA DESA (Studi di Desa pada Kecamatan Langsa Lama) - Nurhalimah; Azhar, Iqlima; Agustina Nurul Fajriah (Jurnal Mahasiswa Akuntansi Samudra, 2024)
This study aims to determine the Effect of Village Apparatus Competence, Information Technology (IT) Utilization, and Clarity of Budget Targets on Village Fund Management (Case Study of Village in Langsa Lama District). The type of data used is primary data and data collection is carried out by distributing questionnaires to respondents. The sample selection in this study used purposive sampling, a sample of 90 respondents was obtained from 15 Village Offices in Langsa Lama District consisting of the Village Head, Village Secretary, Finance Head, Planning Head, Welfare Kasi, and Village Consultative Body (BPD). The data was analyzed using the SPSS (Statistical Product And Service Solutions) program. The analysis methods used are data quality tests, classical assumption tests, and multiple linear regression analysis. The results of this study show that the competence of Village Apparatus partially has a significant influence on Village Fund Management. Technology Utilization.